THE ROLE OF PERSONAL INNOVATIVENESS ON BEHAVIORAL INTENTION OF INFORMATION TECHNOLOGY - Melissa T. A. Simarmata; Iman Jaya Hia (Journal of Economic and Business, 2020)
The purpose of this study is to investigate PIIT as an appropriate factor in predicting behavioral intention in the information technology acceptance framework. This research is a longitudinal study conducted during one semester in the spring semester of 2017. Data collection using a survey questionnaire in the pilot study, period 1 and period 2. Participants in this study are accounting students who are enrolled in Introductory to Computer Application course at the University of HKBP Nommensen, Medan. Statistics techniques used were Pearson Correlation, means, linear regression and paired sample t-test. The results show that the hypothesis and the research model were supported significant statistically. The finding also suggested that the use of IT overtime increased the innovativeness and intention of the students. This research contributed to conducting training using certain software in practical settings.